Mapeamento da susceptibilidade á incêndios através de Sensoriamento Remoto no município de Cáceres - Souza, Felipe N. [UNESP]; Negri, Rogério G. [UNESP]; Gino, Vinicius L.S. [UNESP]; Simões, José V.O. [UNESP] (My University, 2022)
Recently, fire events recorded in Brazil have motivated the application of Remote Sensing and Machine Learning techniques in order to enable the monitoring and prevention of the impacts associated with these events. In this way, the present project aims to map the susceptibility to fires in forest regions through the application of Logistic Regression, built on the basis of the extraction of statistical descriptors under spectral indices.
Mapping susceptibility to fires through remote sensing in the municipality of Cáceres